A Cross-Destination Analysis of Country Image: A Key Factor of Tourism Marketing - Marinao-Artigas, E (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
The purpose of this study is to check whether the image of a country can be configured by the interaction of cognitive and emotional experiences with the functional, hedonic, and symbolic benefits perceived by the visitor. It is intended to verify whether this multidimensional image facilitates the connection between people s familiarity with the country, its reputation, and their satisfaction. A non-probabilistic convenience sample has been used. An online questionnaire has been applied. In total, 1812 valid answers have been obtained. Through a structural equations model (SEM), the quantitative analysis has been developed. This study revealed that the country s image has a multidimensional configuration that positively connects people s familiarity with a country with its reputation and with visitor satisfaction. This proposed new approach to configure the image of a country based on its visitors can be a key tool for implementing destination marketing strategies. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.